FEATURES OF SELF-ESTEEM OF A MODERN TEENAGER - Zhubanazarova N.S.; Madaliуeva Z.B.; Silerova Edita; Toxanbayeva N.K.; Narege G.; Sadykova N.M.; Sailinova K.K. (Scientific Journal of Pedagogy and Economics, 2020)
Socio-economic changes in modern society have a significant impact on the formation of the personality of the future generation and the level of their socio-psychological adaptation. This occurs in adolescence, characterized by contraindications. Adolescence includes such complex changes as the formation of self-awareness and behavior, self-esteem and the development of an independent, independent system of self-esteem and selfesteem. Such conditions provided the basis for a broad discussion of evaluation at this stage of development. At the same time, along with various psychological and social factors, self-esteem contributes to the normal implementation of the socialization of the child and the norms of social behavior. The article reveals the essence of the concept of “self-esteem” of psychological characteristics of a modern teenager in the personal development of a modern teenager, forms a structural model of self-esteem on the basis of this theoretical knowledge and defines the characteristics of self-esteem of adolescents in modern conditions of training and education. On its basis, the features of self- assessment of students in grades 7-10. It is also important to apply this scientific work to improve the interaction and understanding of adolescents in the family and to train teachers working with adolescents.